Specific Inactivation of Herpes Simplex Virus by Silver Nitrate at Low Concentrations and Biological Activities of the Inactivated Virus - Shimizu, Fumio (1976)
The infectivities of herpes simplex virus types 1 and 2 were inactivated by silver nitrate at concentrations of 30 μM or less, which did not affect at all the infectivities of hemagglutinating virus of Japan, vesicular stomatitis virus, poliovirus, vaccinia virus, and adenovirus. The inactivated virus retained the capability of adsorbing to the cell, with an adsorption kinetics quite similar to that of intact virus, and of inducing the concanavalin A agglutinability in the infected cells, whereas it lost completely the capability of producing viral antigens and other cytopathic changes.